The development of students’ communication competence to improve the effectivenessof foreign language learning - Olga N. Tsypkina; Polina G. Labzina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The necessity of students’ communication skills development and their readiness to work with professional literature both in Russian and foreign languages is mentioned in the article. The theoretical analysis let us prove that the success of the process mentioned depends not only on knowledge and exercises but on the communicative abilities of a personality. The solving of the problem of developing student’s communication competence specifies an important role of cognitive problems in the process of dealing with scientific discourse encouraging making up of the personality which is ready for the future professional activity. Communicative-cognitive problems answer to this purpose. They are aimed at perception, understanding and creating discourse as the processes mentioned above require such mental operations as analysis, synthesis, comparison, generalization, specification, abstracting in the communication process.